PERBANDINGAN FREKUENSI SAKIT PADA BAYI USIA 6-9 BULAN BERDASARKAN POLA MENYUSUI - Oktalia " Devega; Riri " Novayelinda; Safri " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Breastmilk can prevent disease during infancy and childhood. The goal of this study was to determine the difference in 6-9 months infant morbidity based on the type of breastfed pattern. The design of this study was prospective cohort study with comparative study. The population of this study was all of infants who were initiate breastfeeding soon after delivery. The sample of this study was 49 infants which were divided into 16 exclusive breastfeeding, 17 predominant breastfeeding and 16 partial breastfeeding by using purposive sampling technique which was evaluated using observation sheet to evaluate the infant morbidity. This study was analyzed using non parametric Kruskal-Wallis test and Post-hoc Mann Whitney. The statistical results showed that there was difference in 6-9 months infant morbidity based on the type of breastfed pattern (p value (0,035) <α (0.05)). The Post-hoc test showed that there was difference in infant morbidity between exclusively vs partially breastfed group (p value (0,015) <α (0.05)), whereas there was no difference in another group. Based on the result of the research, it can be concluded that exclusive breastfeeding during 6 months of life can decrease the 6-9 months infant morbidity, so that the study recommends infants were exclusive breastfeeding during 6 months of life. Key Words: Exclusive Breastfeeding, Infant Morbidity, Partial Breastfeeding, Predominant Breastfeeding